Effects of Dietary Choline Levels During Pregnancy on Reproductive Performance, Plasma Metabolome and Gut Microbiota of Sows - Zhong, Wei; Hu, Liang; Zhao, Yang; Li, Zhen; Zhuo, Yong; Jiang, Xuemei; Li, Jian; Zhao, Xilun; Che, Lianqiang; Feng, Bin; Lin, Yan; Xu, Shengyu; et al. (Frontiers in Veterinary Science, 2022)
This study investigated the effects of dietary choline levels during gestation on reproductive performance of sows. In addition, the plasma metabolome and gut microbiota of sows was studied. A total of 260 multiparous sows were allocated to five dietary treatment groups with increasing choline concentrations (1050, 1450, 1850, 2250, and 2650 mg/kg) in a randomized complete block design. The sows were fed experimental diets from breeding until farrowing and a common lactating diet during lactation. The results showed that the backfat (BF) gain of sows during gestation, individual birth weight for total piglets born, piglets born alive, average piglet weight at weaning increased linearly (P < 0.05), whereas the within-litter birth weight variation coefficient (CV) of piglets born alive and suckling piglet mortality decreased linearly (P < 0.05) as dietary choline level increased. A quadratic effect of dietary choline level was observed for the average daily feed intake (ADFI) of sows during lactation (P < 0.05). ADFI was maximized when the dietary choline concentration reached 1910 mg/kg. Plasma H2O2 concentration at day 30 of gestation in the 1050 mg/kg group was greater than that in the 1850 and 2650 mg/kg groups (P < 0.05). Plasma metabolomics identified 46 metabolites among the three groups. Specifically, plasma concentrations of trimethylamine-N-oxide (TMAO), dopamine, and L-proline increased while 1-methylhistidine concentration decreased as dietary choline levels increased. In addition, bacterial observed species and richness (Chao 1 and ACE) at day 110 of gestation decreased as dietary choline levels increased (P < 0.05). For the gut microbiota composition, the enhanced dietary choline level decreased the abundance of phylum Proteobacteria (P < 0.05) and increased the abundance of phylum Actinobacteria (P < 0.05) at day 30 of gestation. Compared with the 1050 mg/kg group, the abundance of genus Terrisporobacter was less in the 1850 mg/kg group, and genera Bacillus and Cellulomonas were greater in the 2650 mg/kg group. In summary, increasing dietary choline levels improved the birth weight, uniformity of neonatal piglets and litter performance during lactation. This may be associated with better antioxidant capability, metabolic status, and gut microbiota of sows during gestation.